2013
DOI: 10.1155/2013/182516
|View full text |Cite
|
Sign up to set email alerts
|

Increased Female MS Incidence and Differences in Gender-Specific Risk in Medium- and High-Risk Regions in Finland from 1981–2010

Abstract: Background. MS incidence has increased among females, suggesting the presence of environmental effect. Object. Regional differences and temporal changes in gender-specific MS incidence were studied in Finland. Methods. Cases from Jan 1, 1981 to Dec 31, 2010 in Pirkanmaa, Seinäjoki and Vaasa districts were included. The standardized incidence rates (SIR), incidences per 105 person years with 95% confidence intervals (CI), and female-to-male ratios (F/M) were determined by district. Results. 1617 cases were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…As the recent incidence and sex difference seem to have stabilized and the global trends in mortality have decreased, the general increase in prevalence is largely explained by increasing survival in MS population, which may largely explain for the ten‐year change also in our data. The incidence up to 2010 in the three hospital districts under study has earlier shown high female versus male ratios and both increase (in Pirkanmaa) and stability (in Seinäjoki and Vaasa) in total trends . The earlier reported concurrent standardized mortality ratios up to 2006 in a Finnish cohort (including Seinäjoki, Vaasa, and southern Uusimaa districts) diagnosed from 1964 to 1993 were shown to be higher among women as compared to men .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As the recent incidence and sex difference seem to have stabilized and the global trends in mortality have decreased, the general increase in prevalence is largely explained by increasing survival in MS population, which may largely explain for the ten‐year change also in our data. The incidence up to 2010 in the three hospital districts under study has earlier shown high female versus male ratios and both increase (in Pirkanmaa) and stability (in Seinäjoki and Vaasa) in total trends . The earlier reported concurrent standardized mortality ratios up to 2006 in a Finnish cohort (including Seinäjoki, Vaasa, and southern Uusimaa districts) diagnosed from 1964 to 1993 were shown to be higher among women as compared to men .…”
Section: Discussionmentioning
confidence: 79%
“…The incidence up to 2010 in the three hospital districts under study has earlier shown high female versus male ratios and both increase (in Pirkanmaa) and stability (in Seinäjoki and Vaasa) in total trends. 18 The earlier reported concurrent standardized mortality ratios up to 2006 in a Finnish cohort (including Seinäjoki, Vaasa, and southern Uusimaa districts) diagnosed from 1964 to 1993 were shown to be higher among women as compared to men. 19 The relative impact of both sex-specific incidence change and the sex-specific mortality risk may be reflected in the age-specific standardized prevalence change, where peak among women remained in the 40 to 49-year group, but moved from 50-59 years to 40-49 years among men.…”
Section: Discussionmentioning
confidence: 96%
“…The question about a gender ratio of GBS incidence therefore remains unsolved. Considering this, it is interesting to note that the incidence of multiple sclerosis, another autoimmune disorder, has increased particularly in women in Northern Finland (Krökki et al, ; Holmberg et al, ) and in the Netherlands (Kramer et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990´s, the prevalence of MS in Finland varied by region between 100 and 200/100 000 and incidence between 5 and 12/100 000 person‐years . In 2010, the incidence of MS in the western regions of Finland was 6.7‐12.5/100 000 person‐years and had increased over 30 years (1981‐2010), especially in the region of Ostrobothnia, which had a high incidence at the outset . During these three decades, the incidence had risen especially among females and the female‐to‐male ratio had increased …”
Section: Introductionmentioning
confidence: 99%